Logistics Cost Dynamics in International Business: A Causal Approach. Issue 4 (November 2020) - Kar, Ashutosh; Datta, Pratyay Ranjan
The cost of logistics plays a vital role in the pricing of goods in international trade. Besides, the recent imposition of additional tariff by even upper-middle income countries such as the USA, China etc., has led to an increase in the total landed cost of goods. However, a seller has no option but to adapt to changing tariff requirements and can articulate only the logistics cost to a certain extent. This aspect requires an understanding of the logistics cost dynamics in international business. Since a higher volume of goods moves by marine transportation, this study focusses on the same. In this article, authors have attempted to establish a statistically significant relationship between prices and other factors like fuel, number of vessels, freight, and weight value ratio. The paper introduces a logistics-coefficient to indicate the extent of integration of logistics activities to keep the total-landed-cost (TLC) unchanged. Finally, the author proposes the system dynamics model to study the impact of changes in any one or some or all these factors on the price of the product. This model will enable the global firm to decide the entry and exit in the market. JEL Codes: F23